Effective Channels for Establishing an Irlen Centre to Help People with Reading Problems in Thailand - Petcharat Lovichakorntikul (Information Management and Business Review, 2011)
Irlen Syndrome was identified in the 1980s as a condition that affects people who cannot see written text on a page properly. Consequently, their ability to learn in a standard educational setting is significantly limited and their future lives constrained. Further, affected people, in common with people with dyslexia, are often accused of lack of intellect or interest in studies and this can be a source of stress and relationship breakdown. The eponymous Irlen method provides a technical solution to the problem involving coloured lenses, which helps some people. Nevertheless, the approach falls between the educational and medical worlds and this provides some credibility issues. This paper examines the possibility of establishing an effective and profitable Irlen Centre in Thailand through personal, in-depth interviews with relevant professionals in a variety of fields. The findings are considered in the light of contemporary Thai culture and the pressure on young people to take an active part in a market-oriented society.